Iceland as Norm Entrepreneur : Implementing Innovation in the Measurement of Economic Progress - Johanna E. Van Schalkwyk 1973- (2016)
Concerns have been raised internationally about the environmental and social sustainability of policies focused solely on economic growth. Economic growth is most often represented by gross domestic product (GDP), the most universal economic indicator. GDP, however, through its inherent flaws, presents a skewed impression of actual contributions to the economy, as well as giving a positive value to, amongst other things, harmful environmental events. In the last few decades, there has been rising dissatisfaction with the prominence of GDP and how this may steer public policy and private enterprise in a direction detrimental to a sustainable future for humanity. This thesis explores the flaws of GDP and the possibility of Iceland acting as a norm entrepreneur in the implementation of much called for innovation in measuring economic progress. Nordic countries have been known to effect greater social and political change on an international platform than their size would suggest. The findings of this research show that Iceland can have a role to play in implementing innovation in economic measurements. However, the question remains whether a relatively young republic, which is still battling with its own national identity in the global arena, can muster the political will to do so.